PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI MENGIKUTI UJIAN SERTIFIKASI PROFESI AKUNTANSI - Binna Wahyu Lestari, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2019)
The purpose of this study is to find out whether quality motivation, career motivation and economic motivation affect the students' participation in the Accounting Professional Certification Examination. This study uses quantitative methods. The sampling technique in this study with non-probability sampling method with purposive sampling technique, by determining the number of respondents 100 of the total population of 439 undergraduate students of the Faculty of Economics Accounting Study Program at Slamet Riyadi University, Surakarta. Data analysis in this study uses Multiple Linear Regression Analysis. Data analysis techniques using classical assumption test, multiple linear regression analysis, t test, F test, and determination coefficient. The results showed that: quality motivation had a positive and significant effect on students' interest in taking the Accounting Professional Certification Examination, career motivation had a positive and insignificant effect on students' interest in taking the Accounting Professional Certification Examination, and economic motivation had a positive and insignificant effect on students' interest in taking the Certification Exam Accounting Profession. Keywords: economic motivation, career motivation, economic motivation, student interest in taking Accounting Professional Certification Examination.